Prognostic Factors Change Over Time After Hepatectomy for Colorectal Liver Metastases: A Multi-institutional, International Analysis of 1099 Patients. Issue 6 (June 2019) - Margonis, Georgios Antonios; Buettner, Stefan; Andreatos, Nikolaos; Wagner, Doris; Sasaki, Kazunari; Barbon, Carlotta; Beer, Andrea; Kamphues, Carsten; Løes, Inger Marie; He, Jin; Pawlik, Timothy M.; Kaczirek, Klaus; et al.
Abstract : Objective: To evaluate the changing impact of genetic and clinicopathologic factors on conditional overall survival (CS) over time in patients with resectable colorectal liver metastasis. Background: CS estimates account for the changing likelihood of survival over time and may reveal the changing impact of prognostic factors as time accrues from the date of surgery. Methods: CS analysis was performed in 1099 patients of an international, multi-institutional cohort. Three-year CS (CS3) estimates at the "xth" year after surgery were calculated as follows: CS3 = CS ( x + 3)/CS ( x ). The standardized difference ( d ) between CS3 rates was used to estimate the changing prognostic power of selected variables over time. A d < 0.1 indicated very small differences between groups, 0.1 ⩽ d < 0.3 indicated small differences, 0.3 ⩽ d < 0.5 indicated moderate differences, and d ≥ 0.5 indicated strong differences. Results: According to OS estimates calculated at the time of surgery, the presence of BRAF and KRAS mutations, R1 margin status, resected extrahepatic disease, patient age, primary tumor lymph node metastasis, tumor number, and carcinoembryonic antigen levels independently predicted worse survival. However, when temporal changes in the prognostic impact of these variables were considered using CS3 estimates, BRAF mutation dominated prognosis during the first year ( d = 0.48), whereas surgeon-related variables (ie, surgical margin and resected extrahepatic disease) determined prognosis thereafter ( d ≥ 0.5). Traditional clinicopathologic factors affected survival constantly, but only to a moderate degree (0.3 ⩽ d < 0.5). Conclusions: The impact of genetic, surgery-related, and clinicopathologic factors on OS and CS3 changed dramatically over time. Specifically, BRAF mutation status dominated prognosis in the first year, whereas positive surgical margins and resected extrahepatic disease determined prognosis thereafter. Abstract : Supplemental Digital Content is available in the text